5(r+7)+5+3r=7(r+2)-4r+1

Simple and best practice solution for 5(r+7)+5+3r=7(r+2)-4r+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(r+7)+5+3r=7(r+2)-4r+1 equation:



5(r+7)+5+3r=7(r+2)-4r+1
We move all terms to the left:
5(r+7)+5+3r-(7(r+2)-4r+1)=0
We add all the numbers together, and all the variables
3r+5(r+7)-(7(r+2)-4r+1)+5=0
We multiply parentheses
3r+5r-(7(r+2)-4r+1)+35+5=0
We calculate terms in parentheses: -(7(r+2)-4r+1), so:
7(r+2)-4r+1
We add all the numbers together, and all the variables
-4r+7(r+2)+1
We multiply parentheses
-4r+7r+14+1
We add all the numbers together, and all the variables
3r+15
Back to the equation:
-(3r+15)
We add all the numbers together, and all the variables
8r-(3r+15)+40=0
We get rid of parentheses
8r-3r-15+40=0
We add all the numbers together, and all the variables
5r+25=0
We move all terms containing r to the left, all other terms to the right
5r=-25
r=-25/5
r=-5

See similar equations:

| x/13*10=109 | | 21+t=-3 | | -14x−5=-10x-45−10x−45 | | 291=m+–453 | | 2x8±8=20 | | -4w+3=-9 | | 7x+35=4x+50 | | 33/4x=371/2 | | x-111=180 | | (2x-3)×2=2 | | 9x12=3X+18 | | -48-3m2=8m-4m2 | | 3/4x+1/4x=1x | | (5x-6)(4x+16)=0 | | 11-x+8=9x+6=7x+20 | | -48m-3m2=8m-4m2 | | 2x+4-5x(x=5) | | x+130=90 | | 36-4c=-2c-14 | | (2x+20)+72+46=180 | | 36−4c=−2c−14 | | c−-496=993 | | 10y-20=5y+40 | | c−–496=993 | | 2(5x-4)=9x | | 4y(2y−1)=−2y+1. | | 1/3(6x+9)=2x+4 | | 200m-100m+53625=55275-175m | | x6+3=-79 | | 8=9x-29 | | 2/7x-8=1/7x+11 | | 6(2x-3)=4(3x-2)-8x-8 |

Equations solver categories